Weighted Boundedness of Toeplitz Type Operator Associated to General Singular Integral Operator Satisfying a Variant of Hörmander’s Condition (Analysis in Theory and Applications, 2025)
In this paper, we establish the weighted sharp maximal function inequalities for the Toeplitz type operator associated to the general singular integral operator satisfying a variant of Hörmander's condition. As an application, we obtain the boundedness of the operator on weighted Lebesgue and Morrey spaces.
Keywords: Toeplitz type operator; singular integral operator; sharp maximal function; weighted BMO; weighted Lipschitz function.